International Journal of Water Resources DEVELOPMENT - International Journal of Water Resources DEVELOPMENT (Taylor & Francis, 2026)
The mission of the International Journal of Water Resources Development is to advance understanding of the dynamic and evolving relationships between human and water, and to contribute to improved water governance worldwide.
FI 0.65
Q3
Keywords: Geography; Planning; Urban & Environment; Acuerdos transformativos; Transformative agreements; Recursos hídricos; Política del agua; Gestión del agua